Evaluation of busulfan, cyclophosphamide, and etoposide as a preparation regimen for autologous stem cell transplantation in Hodgkin's lymphoma patients - Bicim, Soykan; Erkurt, Mehmet Ali; Kuku, Irfan; Kaya, Emin; Berber, Ilhami; Kaya, Ahmet; Ozen, Ilknur Nizam (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Hodgkin's lymphoma (HL) exhibits a cure rate of 90% in patients diagnosed at an early stage and a cure rate ranging from 70% to 90% in patients diagnosed at an advanced stage. In the case of patients with relapsed/refractory HL (r/rHL), it is recommended to provide salvage chemotherapy initially, followed by autologous stem cell transplantation (ASCT). The ideal conditioning regimen for the transplantation process is still being investigated.OBJECTIVES: For individuals with r/rHL, high-dose chemotherapy combined with ASCT (HD-ASCT) is thought to be the most effective method of treatment. The purpose of this research was to evaluate the effectiveness and safety of the busulfan, cyclophosphamide, and etoposide (BuCyE) preparation regimen in r/rHL patients.MATERIALS AND METHODS: Retrospective analysis was conducted on the data of 67 lymphoma patients older than 18 years who had HD-ASCT with the BuCyE conditioning regimen between September 2014 and November 2021 (86 months). The research consisted of 34 r/r HL patients among them. A parenteral regimen of 0.8 mg/kg of busulfan every 6 h from day -7 to day -5, 50 mg/kg of cyclophosphamide on days -3 and -2, and 400 mg/m2 of etoposide on days -5 and -4 comprised the patient preparation regimen before ASCT. All data were collected from inpatient files and the Inonu University Turgut Ozal Medical Center Hospital Information System.RESULTS: The median age of the patients was 43 years, and 67.6% were males. The most common type of HL was nodular sclerosis, which was followed by mixed cellularity. The median time for platelet and neutrophil engraftment was 14 and 11 days, respectively. 5.0 x 106/kg was the median transplanted dose of CD34+ cells (2.1-13.55). Liver toxicity was observed in 6 (17.6%) patients. Eight patients suffered from pulmonary side effects. The median number of previous chemotherapies was 2 (2-4). In all lymphoma patients, the complete response rate was 61.8% (n = 21), whereas the disease progression rate was 32.3% (n = 11). Transplantation-related mortality on the 100th day was 8.8% (n = 3). Three-year overall survival was 57.17%.CONCLUSION: When the literature was reviewed, the studies with the BuCyE preparation regimen in patients with r/rHL were limited. This conditioning regimen was found to have fewer side effects and a lower cost. It can be preferable when compared to carmustine (BCNU), etoposide, cytarabine (ARA-C), and melphalan (known as BEAM) in r/rHL.
Keywords: Busulfan; cyclophosphamide; etoposide; Hodgkin's lymphoma; stem cell transplantation